Effect of Salvia officinalis on Thyroid Gland Function in Male Rats - Ihsan Raisan Ibrahim (Journal of Global Pharma Technology, 2019)
The objective of the current study is to evaluate the protective role of Saliva officinalis extract against carbimazole that induce hypothyroidism. Experimental albino rats were divided into four groups, first group considered as a control group. While other three groups administrated Saliva officinalis extract, carbimazole and Salvia officinalis extract and carbimazole respectively. Rats were scarified at the end of experimental and blood samples collected. T4, T3 and TSH levels were assayed and data underwent statistical analysis. Results showed that T4 and T3 levels significantly increased in rat’s administrated Saliva officinalis extract compared to the control group. While carbimazole significantly reduced these hormones in comparison with other groups. On the other hand, treatment rats with Salvia officinalis and carbimazole increase T3 and T4 significantly. TSH significantly elevated in rats treated with carbimazole compared to groups treated with Saliva officinalis, carbimazole and Saliva officinalis respectively. It’s concluded that Salvia officinalis reduced effects induced by carbimazole in thyroid function.Keywords: Salvia officinalis, Thyroid hormones, Carbimazole.